PENGARUH STRATEGI DIFERENSIASI TERHADAP KINERJA UMKM: KEUNGGULAN KOMPETITIF SEBAGAI MEDIATOR - Nisa, Sri Hijratun; Animah, Animah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024DO - 10.24843/EEB.2024.v13.i05.p19, 2024)
This research explores how differentiation strategies influence the performance results of micro, small, and medium enterprises (MSMEs) in the creative domain of pearl gold craftsmanship in Mataram City. The investigation is based on the resource-based view (RBV) theory. Competitive advantage is used as a mediator variable in the relationship. Data were collected from 57 MSME artisans in the pearl gold craft industry in Sekarbela Craft Center, Mataram City. The data was analyzed using quantitative methods and path analysis. The results showed that differentiation strategies have a positive and significant effect on competitive advantage and MSME performance. Competitive advantage has a significant effect on the performance of MSMEs. However, competitive advantage is not proven to provide a significant mediating influence in the relationship between differentiation strategy and MSME performance. The direct influence of implementing a differentiation strategy on the performance of MSMEs surpasses its indirect influence achieved through competitive advantage. This finding underscores the importance of differentiation strategies in improving MSME performance, particularly in industries that emphasize product differentiation and new designs. This research provides practical implications for MSMEs in the pearl gold craft creative industry in Mataram City in developing differentiation strategies to improve business performance.